Genistein: Its Role in Breast Cancer Growth and Metastasis - Mukund, Vidya (Current Drug Metabolism, 2020)
Background: Genistein being a phytoestrogen imitates the characteristics of estrogen, which can be useful to treat conditions by reducing the estrogen levels at the time of menopause, osteoporosis and high risk for breast cancer. Objective: The superior binding of genistein to ERβ might help in reducing breast malignancy risk. Conclusion: Genistein induces cell cycle arrest, anti-metastatic properties and ultimately affects the breast cancer cell growth by multiple mechanisms. Genistein-mediated anti-proliferative or anti-growth effects are usually observed at higher concentrations. These signaling pathways involve the decrease of NF-ΚB, HIF-1α, VEGF, and an increase of tumor suppressor p21. This will provide further insight into understanding the biology of transcription factors NF-ΚB, and HIF-1α in breast cancer.
Keywords: cell proliferation